2015
DOI: 10.1017/s2045796015000633
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of the Italian version of the Reported and Intended Behaviour Scale (RIBS)

Abstract: The RIBS-I demonstrated good psychometric properties and it can be considered a useful tool to: (1) assess stigmatising (actual or potential) behaviours in the general population; (2) test the efficacy of anti-stigma campaigns and actions; (3) design further studies to better understand the relationship between the three different components of stigmatisation: knowledge, attitudes and behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
5
20
0
Order By: Relevance
“…As suggested by Evans-Lacko et al (2011) responses to item eight may be mediated by higher reports of having a friend experiencing a mental health problem in item four. Despite showing more normally distributed results overall, similar patterns of responses were previously found in Japanese and Italian adult validation studies (Pingani et al, 2016;Yamaguchi et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As suggested by Evans-Lacko et al (2011) responses to item eight may be mediated by higher reports of having a friend experiencing a mental health problem in item four. Despite showing more normally distributed results overall, similar patterns of responses were previously found in Japanese and Italian adult validation studies (Pingani et al, 2016;Yamaguchi et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…The criteria used for assessing good model fit was an RMSEA value of <.06 and CFI and TLI values >.95 (Hu & Bentler, 1999). Factor structure was examined by conducting CFA for two-latent factors, reported and intended behaviors, previously confirmed with university student and adult samples (Pingani et al, 2016;Yamaguchi et al, 2014 Differences in responses to reported and intended behavior items were explored using group measurement invariance. Specifically, differential item functioning (DIF) comparing gender and age group was examined in a multiple indicator multiple cause (MIMIC) model.…”
Section: Discussionmentioning
confidence: 99%
“…Intended behavior toward people with mental health problems was assessed through the Reported and Intended Behavior Scale [RIBS (43, 44)]. The RIBS is composed of eight items that come in two groups of four: the first four items (1–4) focus on previous experiences with people affected by mental illness (i.e., lived with, worked with, lived nearby, or had a relationship with a person with a mental health problem); the second group (58) focuses on future intentions to establish contact with people affected by mental health problems (i.e., live with, work with, live nearby, or have a relationship with a person with mental illness).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, even in those partial data it shows potential for use in improving safety at the construction sites using scaffolds. Also, according to several authors, the goodness-of-fit (GF) model had to be considered first [9,17,7,18]. Within the GF model, it is necessary to consider three indicators: measure of absolute fit, measure of increased fit and measure of decreased fit (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of SURAM is the core part of the 'ORKWIZ' project. The research also shows that many accidents can be avoided by developing a proper concept of safety assurance at the preparation stage [5,6,7].…”
Section: Introductionmentioning
confidence: 87%